Problems of Students Understanding of Zakat Material in The Digital Era Case Study of Al Mukhlisin Islamic Boarding School - Tahir, Muhyiddin; Sermayana, Andi; Muhsyanur, Muhsyanur (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This article examines santri's understanding of zakat in the digital era as well as the problems they face at Pondok Pesantren Al-Mukhlisin DDI Paria, Majauleng District, Wajo Regency. The main focus of this study is to answer three important questions: (1) How is the santri's understanding of zakat material in the digital era? (2) How is the problematic understanding faced by santri about zakat material in the digital era? (3) How is the strategy to overcome the problematic understanding of santri about zakat material in the digital era case study at Al-Mukhlisin DDI Paria Islamic Boarding School, Majauleng District, Wajo Regency? The type of research used is qualitative. The research location was at the Al-Mukhlisin DDI Paria Islamic Boarding School, Majauleng District, Wajo Regency, which was carried out for approximately 3 months. The approaches used are phenomenological, participatory, case study and educational. Methods in collecting data through observation, interviews and documentation. The research instruments used were human instruments, interview guidelines, observation guidelines and documentation record formats. After the data is collected, it is then analyzed through 3 stages, namely: data reduction, data presentation and data verification or conclusion drawing. For the validity of the research, credibility, defendability, confirmability and transperebility tests were carried out. The results showed that (1) santri understanding of zakat material in the digital era varies, some have a good understanding while others experience confusion due to lack of digital literacy and learning practices. (2) Problems in students' understanding of zakat material include difficulties in understanding zakat material, as well as limitations in the learning process meeting. (3) The strategy to overcome the problems of students' understanding, teachers are expected to not only provide basic knowledge about zakat material but also teach in the form of practice and the digital era to get information about zakat material, and guide students in dealing with changes caused in the digital era.